THE INFLUENCE OF ATORVASTATIN AND ROSUVASTATIN IN ATHEROSCLEROSIS ON THE PARAMETERS OF CELLULAR IMMUNITY AND IN VITRO LEUCOCYTE ACTIVATION - A. Yu. Filatova; A. V. Potekhina; N. Yu. Ruleva; N. V. Radyukhina; T. I. Arefieva (Российский кардиологический журнал)
Aim. To compare the influence of “lipophilic” atorvastatin and “hydrophilic” rosuvastatin on the parameters of cellular immunity in atherosclerosis patients.Material and methods. Totally, 35 participants included, mean age 62 [57;68] y.o., 18 males and 17 females, directed for follow-up to Myasnikov Cardiovascular Center with preliminary diagnosis coronary heart disease, atherosclerosis of coronary and carotid arteries, and with indications for intensified statin therapy. In 17 patients the dosage of atorvastatin was increased from 20 to 80 mg, in 18 — dosage of rosuvastatin from 10 to 40 mg. All patients at baseline and in 1 month, by the methods of direct immune fluorescence and cytofluometry underwent the measurement of content of monocytes and lymphocyte populations in peripheral blood, incl. regulatory and effectory subpopulations of the latter. Under the circumstances of cellular culture the influence studied, of atorvastatin and rosuvastatin on CD4+ T-lymphocytes populations, as the lipopolysaccharideinduced synthesis of cytokines by monocytes of donors blood.Results. At the background of atorvastatin, there was marked increase of relative content of circulating regulatory T-lymphocytes (Treg), increase of the relation of Treg/Thelper 17 (Th17) and changes of cellular immunity parameters. Statins did not influence subpopulations of blood monocytes. There was dose-dependent inhibition by statins of CD4+ T-lymphocytes proliferation: atorvastatin action was noted in 10 nM/L, rosuvastatin — in 10 times higher concentration. Introduction ofstatins, 10-100 nM/L, to the culture of monocytes did not influence neither spontaneous, nor endotoxin induced secretion of cytokines.Conclusion. In therapeutic dosages atorvastatin shows immune modulating activity presenting with an increase of relative content of regulatory T-lymphocytes subpopulations that might be determined by suppression of effectory cells proliferation.